Hubungan Dukungan Suami dan Peran Petugas Kesehatan dalam Pemilihan Penolong Persalinan pada Ibu Hamil Trimester III di Puskesmas Gedung Rejo Sakti Kecamatan Penawar Aji Tulang Bawang Tahun 2021 - Mastuti, Hilda; Febriyanti, Hellen (Ners Akademika, 2022)
Purpose: The research objective is to know the relationship between husband support and the role of health workers in the selection of birth attendants at the Puskesmas Gedung Rejo Sakti, Penawar Aji Tulang Bawang district. Method: The type of research used is quantitative analytical design research with a cross-sectional approach. The population in this research were the elderly who visited the Public Health Center of Kalibalangan, namely 129 elderlies. The sample in this research amounted to 56. Gamma Somer's used in test analysis. This type of research is quantitative with cross sectional approach. The study population was TM III pregnant women with a sample of 91 respondents. The object of this research is the husband's support and the role of health workers and the selection of birth attendants. The research was carried out at the public health center, Gedung Rejo Sakti, onion bone bidder sub-district in February-March 2021. The data was collected using a questionnaire. Data analysis was univariate and bivariate (chi square). Results: The results showed that out of 68 respondents, 16 (26.5%) of respondents chose birth attendants by non-health workers, and 50 (73.5%) respondents chose birth attendants by health workers. As many as 23 (33.8%) respondents with negative husband support and 45 (66.2%) respondents with positive husband support. As many as 21 (30.9%) Respondents did not have support for the role of health workers and as many as 47 (69.1%) respondents had support from health workers. There is a relationship between partner support (p-value = 0.010, OR = 10.400), the role of health workers (p-value = 0.010, OR = 9.11) with the selection of birth attendants at the Gedung Rejo Sakti Community Health Center, Penawar Aji Tulang Bawang District.